248 Challenges and opportunities in the integration of pathology consultation into the IGCS project echo global telementoring program. (18th September 2019) - Plotkin, A; Randall, T; Chuang, L; Ng, J; Eiken, M; O'Connor, S; Baker, E; Dinh, T; Rabban, J; Nout, R; Schmeler, K
Abstract : Objectives: The Extension for Community Healthcare Outcomes (ECHO) is a proven model to improve specialty care for underserved communities. The IGCS uses the Project ECHO platform to connect multi-disciplinary teams across disparate regions, through virtual tumor board case discussions and didactic presentations. In the Project ECHO sessions, international pathologists provide pathology review, which is often based on limited imaging embedded in Power Point slide presentations. We present an initial review of our experience integrating pathologists into the IGCS virtual tumor boards. Methods: We solicited feedback from pathologists and clinicians participating in the IGCS ECHO sessions in individual and small group settings. Results: Clinicians appreciate the inclusion of pathology images and teaching in ECHO sessions with good clinical and educational value. However, challenges were noted with engagement and scheduling with in-country pathologists. Challenges noted by the consulting pathologists included: being asked to offer an opinion with limited information or images, poor quality images, lack of the final pathology report, coping with apparent diagnostic errors, lacking an established relationship with the local pathologist, and the local pathologist not always being present to discuss or explain findings. Opportunities identified include: establishing telepathology connections to facilitate case review, leveraging the IGCS Global Curriculum international mentor/local mentor/trainee model to create parallel and synergistic international and local pathologist collaborative relationships beyond ECHO sessions, further program strengthening through international exchange trips for international and local pathologists. Conclusions: Inclusion of pathology experts in Project ECHO sessions is key to successful tumor boards. Addressing the above-noted challenges will strengthen the entire collaboration.